2022
DOI: 10.3390/genes13081446
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics and Methylomics Reveal Adaptive Responses of Digestive and Metabolic Genes to Dietary Shift in Giant and Red Pandas

Abstract: Both the giant panda (Ailuropoda melanoleuca) and red panda (Ailurus fulgens) belong to the order Carnivora, but have changed their dietary habits to eating bamboo exclusively. The convergent evolution characteristics of their morphology, genome and gut flora have been found in the two pandas. However, the research on the convergent adaptation of their digestion and metabolism to the bamboo diet, mediated by the dietary shift of the two pandas at the gene-expression and epigenetic regulation levels, is still l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Bamboo has bitter-tasting substances as a defense mechanism, and the loss of bitter taste receptors is thought to have enabled giant pandas to overcome this challenge [101]. Additionally, epigenetic modifications increasing the expression of thiosulfate sulfurtransferase have also been proposed as an adaptation in red and giant pandas to overcome the toxicity of bamboo [102]. Polar bears underwent a dietary shift to a hypercarnivorous diet, which is thought to have resulted in losses in the copy number of genes associated with a digestive system, (e.g., AMY1B and NOX4) and olfactory receptor genes [103].…”
Section: Non-metabolic Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bamboo has bitter-tasting substances as a defense mechanism, and the loss of bitter taste receptors is thought to have enabled giant pandas to overcome this challenge [101]. Additionally, epigenetic modifications increasing the expression of thiosulfate sulfurtransferase have also been proposed as an adaptation in red and giant pandas to overcome the toxicity of bamboo [102]. Polar bears underwent a dietary shift to a hypercarnivorous diet, which is thought to have resulted in losses in the copy number of genes associated with a digestive system, (e.g., AMY1B and NOX4) and olfactory receptor genes [103].…”
Section: Non-metabolic Adaptationsmentioning
confidence: 99%
“…Vampire bats have a mutational bias favoring cytosine and not favoring thymine, which subsequently increases threonine in their proteomes, enabling them to overcome inherent amino acid limitations in their diet [104]. Convergent epigenetic changes in both red and giant pandas have been proposed as the molecular mechanism behind the differential expression patterns of genes involved in lipid digestion (DGAT2, SLC2A3, and PARL), enabling them to overcome nutritional challenges of their low-lipid diet [102].…”
Section: Non-metabolic Adaptationsmentioning
confidence: 99%
“…Both pandas consume high-nutrient milk during the suckling period, while they exclusively consume low-nutrient bamboo during the adult period. Their morphology, genome, gut microbiota, and gene expression patterns exhibit many convergent evolutionary characteristics [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Research on giant pandas showed that the high expression levels of genes related to cholesterol metabolism and protein digestion and absorption in their early stages of development may help meet their high energy needs for rapid growth and development, while the high expression levels of genes related to metabolism of carbohydrate, amino acid, and protein during the adult period may indicate their high metabolic levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%